Symptomatic Pneumorrhachis - Koktekir, Ender; Tatarli, Necati; Ceylan, Davut; Koktekir, Bengu Ekinci; Akdemir, Gokhan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Pneumorrhachis (PR) is the presence of air within the spinal canal, whether localized in the epidural or in the subarachnoid space. Evidence of intraspinal air, especially in the subarachnoid space, had been thought to be merely a radiological artifact of serious underlying pathology until it was proven that PRs can be related to neurologic symptoms ranging from radicular pain to serious neurologic deficits. The etiologies, pathomechanisms, and natural courses show differences from case to case, with the result that no consistent treatment strategies exist in the literature. Although the conservative treatment modalities seem to be more appropriate in nonsymptomatic cases, treatment strategies in symptomatic cases remain the subject of discussion. In this study, we present two symptomatic cases of PR arising from different causes and review the literature, focusing especially on the symptomatic cases and strategies for treating them.
Keywords: intraspinal air; neurologic deficit; pneumocephalus; pneumorrhachis; pneumothorax; spinal emphysema